Complications From Postmastectomy Radiation Therapy in Patients Undergoing Immediate Breast Reconstruction: A Population-Based Study - Chris Doherty, MD, MPH; J. Andrew McClure, MSc; Nancy N. Baxter, MD, PhD; Muriel Brackstone, MD, PhD (Advances in Radiation Oncology, 2023)
Purpose: Previous studies have shown an increase in the number of women electing for immediate breast reconstruction at the time of mastectomy. Although often not known at the time, some of these women will require postoperative radiation therapy. The purpose of this study was to investigate if exposure to radiation therapy after mastectomy with immediate breast reconstruction is associated with an increased risk of further surgery to manage complications arising from radiation. Methods and Materials: This retrospective, population-based cohort study included all patients who underwent mastectomy with immediate reconstruction from 2007 to 2014 in the province of Ontario, Canada. Exposure to adjuvant radiation therapy was captured using data from Ontario Health. The study outcome was reoperation for breast reconstruction performed during the follow-up window. Cox proportional hazard models were used to assess the effect of radiation therapy exposure on risk of breast reconstruction reoperation. Results: We identified 2342 patients who underwent mastectomy with immediate reconstruction over an 8-year period in Ontario, of whom 378 (16.1%) underwent adjuvant radiation therapy. Patients who received radiation were significantly more likely to undergo reoperation during follow-up (hazard ratio, 1.76; 95% confidence interval, 1.49-2.08; P < .0001). Patients with implant-based reconstructions (n = 1629, 69.6%) were not more likely to undergo reoperation than those with flap-based procedures (n = 713, 30.4%) (hazard ratio, 1.01; 95% confidence interval, 0.85-1.21; P = .885). Conclusions: Adjuvant radiation therapy initiated after mastectomy with immediate breast reconstruction is associated with an increased risk of additional breast reconstruction surgery, regardless of the type of reconstruction used. Patients with breast cancer who choose to undergo immediate reconstruction after mastectomy should be advised that additional reconstruction procedures may be required.